2010
DOI: 10.1302/0301-620x.92b6.22797
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic treatment of the snapping iliopsoas tendon through the central compartment of the hip

Abstract: We undertook a prospective pilot study to determine whether arthroscopic surgery through the central compartment of the hip was effective in the management of a snapping iliopsoas tendon. Seven patients were assessed pre-operatively and at three, six, 12 and 24 months after operation. This included the assessment of pain on a visual analogue scale (VAS) and function using the modified Harris hip score. All the patients had resolution of snapping post-operatively and this persisted at follow-up at two years. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 14 publications
1
56
0
Order By: Relevance
“…The exact location of tendon release is still a matter of debate, with all of the three sites of release showing equivalent results. 9,52 We postulate that this should be according to surgeons' preference and experience.…”
Section: Discussionmentioning
confidence: 99%
“…The exact location of tendon release is still a matter of debate, with all of the three sites of release showing equivalent results. 9,52 We postulate that this should be according to surgeons' preference and experience.…”
Section: Discussionmentioning
confidence: 99%
“…The iliopsoas tendon can be released either at its insertion into the lesser trochanter or via a transcapsular technique at the level of the hip joint [35,49,50]. These procedures can be successfully done either from the lateral decubitus position [42,49] or from the supine position [35,44,[51][52][53]. Iliopsoas release is preceded by diagnostic hip arthroscopy and treatment of concurrent femoroacetabular impingement (FAI) lesions, chondral damage, and labral tears if indicated [35,42,[49][50][51][52][53].…”
Section: Internal Snapping Hipmentioning
confidence: 99%
“…These procedures can be successfully done either from the lateral decubitus position [42,49] or from the supine position [35,44,[51][52][53]. Iliopsoas release is preceded by diagnostic hip arthroscopy and treatment of concurrent femoroacetabular impingement (FAI) lesions, chondral damage, and labral tears if indicated [35,42,[49][50][51][52][53]. By releasing at the lesser trochanter, a number of authors have reported completely relieving snapping in patients and that, after initial hip flexion weakness, strength is ultimately restored and patients return to their preoperative level of activity and work [42,52], including competitive athletics [51].…”
Section: Internal Snapping Hipmentioning
confidence: 99%
See 1 more Smart Citation
“…5). 7,9,10,15,16 When bony impingement (typically pincer or anterior inferior iliac spine prominence), labral pathology, and psoas impingement or internal snapping hip are seen together, the term "triple impingement" has been used. 17 One retrospective review of failed hip arthroscopies noted that 7 out of 24 failures were related to tight iliopsoas and associated labral tearing.…”
Section: Surgical Indications and Expectationsmentioning
confidence: 99%